Transmitting Values of Acceptance Towards the LGBTQ+ Community Through the Use of Digital Tools in the EFL Classroom - Goddard, Max (Advances in Social Sciences Research Journal, 2022)
Studies on teaching English as a Foreign Language (EFL) have become more and more extensive as the global importance of the English language has increased over the past decades. In a similar way, studies on the topic of the use of digital tools in the EFL classroom have also increased. However, these studies have a strong tendency to focus solely on the linguistic acquisition that can be enhanced in the EFL classroom relevant training should be given to teachers regarding different family types with the use of technology and it being incorporated into lessons. Nonetheless, it is thought that digital tools can also be used for other reasons and purposes, like to promote values of acceptance and diversity towards certain collectives, like the LGBTQ+ community. This paper aims to show the results and findings of a study carried out in the University of Alicante to show the efficiency of using Digital Storytelling the EFL classroom in order to promote values of acceptance as well as improve communication skills.